Submolecular regulation of cell transformation by deuterium depleting water exchange reactions in the tricarboxylic acid substrate cycle. (February 2016) - Boros, László G.; D'Agostino, Dominic P.; Katz, Howard E.; Roth, Justine P.; Meuillet, Emmanuelle J.; Somlyai, Gábor
Abstract: The naturally occurring isotope of hydrogen ( 1 H), deuterium ( 2 H), could have an important biological role. Deuterium depleted water delays tumor progression in mice, dogs, cats and humans. Hydratase enzymes of the tricarboxylic acid (TCA) cycle control cell growth and deplete deuterium from redox cofactors, fatty acids and DNA, which undergo hydride ion and hydrogen atom transfer reactions. A model is proposed that emphasizes the terminal complex of mitochondrial electron transport chain reducing molecular oxygen to deuterium depleted water (DDW); this affects gluconeogenesis as well as fatty acid oxidation. In the former, the DDW is thought to diminish the deuteration of sugar-phosphates in the DNA backbone, helping to preserve stability of hydrogen bond networks, possibly protecting against aneuploidy and resisting strand breaks, occurring upon exposure to radiation and certain anticancer chemotherapeutics. DDW is proposed here to link cancer prevention and treatment using natural ketogenic diets, low deuterium drinking water, as well as DDW production as the mitochondrial downstream mechanism of targeted anti-cancer drugs such as Avastin and Glivec. The role of 2 H in biology is a potential missing link to the elusive cancer puzzle seemingly correlated with cancer epidemiology in western populations as a result of excessive 2 H loading from processed carbohydrate intake in place of natural fat consumption.